Retrospective Enhancement of Bibliographic Records with Tables of Contents and Summary Data and the Effect on Collection Usage. Issue 4 (2nd October 2022) - Stevens, Kerrie
ABSTRACT: Library literature has long discussed the addition of table of contents and summary data to enhance bibliographic records for resources in the collection. The retrospective addition of this enhanced data has not been as widely discussed however this also offers great benefits to be considered. Despite the increased cost often associated with retrospectively working on resources already in the library collection, new life can be breathed into the usage of older resources as demonstrated by usage statistics from this particular library that indicate it can be a worthwhile and valuable project to be undertaken. This research-in-practice paper looks at the retrospective enhancement of existing bibliographic records with table of contents and summary data and its influence on an increase in usage of physical resources.